Peran Pendidikan Agama Kristen Dalam Pembentukan Karakter Dan Etika Berbasis Nilai-Nilai Kristen - Rendi Rendi; Gresia Monika Sinaga; Sandra Rosiana Tapilaha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The cultivation and reinforcement of character values in the present time are crucial to address the moral crisis, especially during adolescence. In this age range, teenagers are in the process of seeking their identity, exhibiting excessive courage, prioritizing peer relationships, desiring recognition, developing an interest in the opposite sex, and often being unrealistic. These values are inseparable from the teachings about the triune nature of God and His work. This article aims to explain the role of Christian Religious Education in character formation. The writing employs a qualitative descriptive method, utilizing data collection techniques based on literature studies or references and observations that focus on the process and meaning of Christian Religious Education. It plays a significant role in shaping students’ character in the current era of globalization.